A 3‐Armed Randomized Controlled Trial of Nurses' Continuing Education Meetings on Adverse Drug Reactions. Issue 2 (2015) - Sarayani, Amir; Naderi‐Behdani, Fahimeh; Hadavand, Naser; Javadi, Mohammadreza; Farsad, Fariborz; Hadjibabaie, Molouk; Gholami, Kheirollah
Abstract : Introduction: : Nurses' insufficient knowledge of adverse drug reactions is reported as a barrier to spontaneous reporting. Therefore, CE meetings could be utilized to enhance nurses' competencies. Methods: : In a 3‐armed randomized controlled trial, 496 nurses, working in a tertiary medical center, were randomly allocated to a didactic lecture, brainstorming workshop, or the control group (delayed education). Similar instructors (2 clinical pharmacists) prepared and delivered the educational content to all 3 groups. Outcomes were declarative/procedural knowledge (primary outcome), participation rate, and satisfaction. Knowledge was evaluated using a validated researcher‐made questionnaire in 3 time points: immediately before, immediately after, and 3 months after each session. Participants' satisfaction was assessed immediately after each meeting via a standard tool. Data were analyzed using appropriate parametric and nonparametric tests. Results: : Rate of participation was 37.7% for the lecture group and 47.5% for the workshop group. The workshop participants were significantly more satisfied in comparison with the lecture group (p < .05). Mean knowledge scores were similar at baseline in the 3 study groups (43–47). Immediately after the meeting, knowledge was significantly higher in the lecture group (79.1 ± 11.9 vs 73.7 ± 11.3; p = .01). At the follow‐up, knowledge scores of the lecture and workshop groups were similar, while significantly higher than the control group. However, the reduction of knowledge score was significantly higher in the lecture group (‐13.0 ± 15.9% vs ‐5.7 ± 15.1%, p = .02). Discussion: : Educational interventions can improve nurses' knowledge of adverse drug reactions. Short‐term learning could be achieved with lecture, but the retention of knowledge will be enhanced by simple interactive techniques.